Supplemental Upward Lighting from Underneath to Obtain Higher Marketable Lettuce (Lactuca sativa) Leaf Fresh Weight by Retarding Senescence of Outer Leaves - Zhang, Geng; Shen, Shanqi; Takagaki, Michiko; Kozai, Toyoki; Yamori, Wataru (Frontiers in Plant Science, 2015)
Recently, the so-called “plant factory with artificial lighting” (PFAL) approach has been developed to provide safe and steady food production. Although PFALs can produce high-yielding and high-quality plants, the high plant density in these systems accelerates leaf senescence in the bottom (or outer) leaves owing to shading by the upper (or inner) leaves and by neighboring plants. This decreases yield and increases labor costs for trimming. Thus, the establishment of cultivation methods to retard senescence of outer leaves is an important research goal to improve PFAL yield and profitability. In the present study, we developed an LED lighting apparatus that would optimize light conditions for PFAL cultivation of a leafy vegetable. Lettuce (Lactuca sativa L.) was hydroponically grown under white, red, or blue LEDs, with light provided from above (downward), with or without supplemental upward lighting from underneath the plant. White LEDs proved more appropriate for lettuce growth than red or blue LEDs, and the supplemental lighting retarded the senescence of outer leaves and decreased waste (i.e., dead or low-quality senescent leaves), leading to an improvement of the marketable leaf fresh weight.